Histomorphological spectrum of masses of the nasal cavity, paranasal sinuses and nasopharynx - S Parajuli; A Tuladhar (Association of Clinical Pathologists of Nepal, 2013)
Background: Swellings of nasal cavity, paranasal sinuses and nasopharynx have infl icted man from time immemorial. Nose is the most prominent part of the face with substantial aesthetic and functional signifi cance. A variety of non-neoplastic and neoplastic conditions involve the nasal cavity, paranasal sinuses and nasophaynx, and these are very common lesions encountered in clinical practice. Materials and Methods: This retrospective cross-sectional study was done in the Department of Pathology, Kathmandu Model Hospital for a period of 5 years from August 2007 to August 2012. Demographic data including age, sex and clinical presentation were obtained from the histopathology records. Results: A total of 148 samples of tissue sent for histopathology were studied, out of which 119 were nonneoplastic and 29 were neoplastic lesions. A slight female preponderance was observed. Infl ammatory nasal polyp was the most common non-neoplastic lesions encountered accounting for a total of 106 cases (89%). Similarly, inverted papilloma was the most common benign lesion (6 cases) and nasopharyngeal carcinoma was the most common malignant lesion (5 cases). Conclusion: Sino-nasal masses have various differential diagnoses. Malignancy should be distinguished from non-malignant lesions. A detailed history, clinical examination and most importantly, thorough histopathological evaluation are essential components of workup of patients for timely medical intervention. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 351-355 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7857